Excellent oncological outcomes besides short-term safety of laparoscopic and endoscopic cooperative surgery for gastric gastrointestinal stromal tumor - Harada, Hiroki; Ohashi, Manabu; Hiki, Naoki; Fujisaki, Junko; Hirasawa, Toshiaki; Yamamoto, Yorimasa; Makuuchi, Rie; Ida, Satoshi; Hayami, Masaru; Kumagai, Koshi; Sano, Takeshi; Nunobe, Souya (Endoscopy International Open, 2022)
Background and study aims Laparoscopic and endoscopic cooperative surgery (LECS) for gastric submucosal tumor was developed as a type of minimal local resection and is now widely used in Asian countries. However, the oncological safety of LECS for gastric gastrointestinal stromal tumor (GIST) remains unclear. LECS has potential oncology-related problems that may influence survival outcomes. Furthermore, the feasibility and safety of LECS have not yet been fully established.Patients and methods Patients who were intended to undergo LECS for gastric GIST from 2006 to 2020 were retrospectively selected. The indication for LECS was determined according to the guidelines. The completion of LECS, complications, and survival outcomes of the patients were analyzed.Results Two hundred fifty-nine patients were eligible in this study. According to intraoperative findings, 44 patients underwent local resection without luminal endoscopic procedures. Of the remaining 215 patients, 213 completely underwent LECS, which corresponds to a completion rate of 99.1 %. Six patients (2.8 %) had postoperative complications of Clavien-Dindo classification grade II or higher. Delayed gastric emptying was most commonly found in four patients (1.9 %). Old age (P = 0.0349), female sex (P = 0.0095), tumor located in the lesser curvature (P = 0.0015), and large tumor diameter (P = 0.0232) were significantly more common in patients with complications. The 3-year overall and disease-specific survival rates were 99 % and 100 %, respectively, in 215 patients who were intended to undergo LECS.Conclusions Despite several oncological concerns, LECS for gastric GIST is oncologically safe besides a feasible and safe procedure in the short-term.